Penser les marges en France : l’exemple des territoires de « l’hyper-ruralité » - Samuel Depraz (Bulletin de l’Association de Géographes Français)
Hyper-rural areas defines – in a controversial way – isolated and very low density areas, as suggested by a recent parliamentary report. The term encompasses overlooked spaces, often imbued by depreciative representations about “deep rural areas”, or the “deserted”, “empty diagonal” in France. However, recent demographic trends contradict such a vision and show a quick reconfiguration of very low density areas with the apparition of new attractive economic bases for newcomers. Admittedly, all structural weaknesses depending on distance are not erased: scientific analysis must therefore accommodate the maintained state of vulnerability of hyper-rural areas with the upsurge of new dynamics, in a paradoxical – but typical – situation of spatial fringes. More fundamentally, this paper aims at demonstrating, through the example of hyper-rural areas, the hermeneutic value of the concept of “spatial fringes” for social geography.